Development of Physical Abilities of Taekwondo Athletes - Boleng, Lukas Maria; Louk, Michael Johannes Hadiwijaya (Universitas PGRI Palembang, 2024)
There are improvements in developments and new methods every year in the taekwondo training program as well as equipping athletes with the sports knowledge is very beneficial to the athlete, because the Athlete can correct his mistakes gradually. In improving the ability of athletes in particular athlete athletics PPLP in NTT carried out with various physical exercises activities. Based on the above description that the Development of Physical Ability Athletes Taekwondo PPLP Provincial NTT” has not achieved satisfactory results. This is due to the lack of attention of the coaches to the proram of good training to improve the physical severity of athletes so that athlete's performance is still not maximum. That nutritional status athletes are all normal or not obese. That improved physical workout results are better on formability, strength, and endurance components than on speed, power, and speed endurance.